Oxidative stress-induced p53 activity is enhanced by a redox-sensitive TP53INP1 SUMOylation - Peuget, S (Nature Publishing Group, 2014)
Tumor Protein p53-Induced Nuclear Protein 1 (TP53INP1) is a tumor suppressor that modulates the p53 response to stress. TP53INP1 is one of the key mediators of p53 antioxidant function by promoting the p53 transcriptional activity on its target genes. TP53INP1 expression is deregulated in many types of cancers including pancreatic ductal adenocarcinoma in which its decrease occurs early during the preneoplastic development. In this work, we report that redox-dependent induction of p53 transcriptional activity is enhanced by the oxidative stress-induced SUMOylation of TP53INP1 at lysine 113. This SUMOylation is mediated by PIAS3 and CBX4, two SUMO ligases especially related to the p53 activation upon DNA damage. Importantly, this modification is reversed by three SUMO1-specific proteases SENP1, 2 and 6. Moreover, TP53INP1 SUMOylation induces its binding to p53 in the nucleus under oxidative stress conditions. TP53INP1 mutation at lysine 113 prevents the pro-apoptotic, antiproliferative and antioxidant effects of TP53INP1 by impairing the p53 response on its target genes p21, Bax and PUMA. We conclude that TP53INP1 SUMOylation is essential for the regulation of p53 activity induced by oxidative stress.